Making visible the diversity of gender identity and sexual orientation through advertising - Castelló-Martínez, Araceli (Anuario ThinkEPI, 2023)
In the search for new market niches, the LGBTQIA+ community has emerged as a population group on which brands have focused. Their creative strategies strive to offer advertising stories that make the diversity of gender identity and sexual orientation visible in a positive way, focusing on actual reality. The defense of plurality, in this sense, converges with so-called brand activism, with which companies aim to show transparency and commitment and convey a sense of listening, reflecting their contribution to the improvement of society in their communication strategies. The discussion herein offers a review of more than 20 examples that illustrate how advertising communication has a great responsibility toward society as an emotional space and a space for advocacy and social change.